‘C’était moi mais ce n’était pas moi’: portrayal of the disabled body in Catherine Breillat’s Abus de faiblesse (2013) - Dooley, Kath (Routledge, 2018)
Writer/director Catherine Breillat’s most recent film, Abus de faiblesse (2013), explores an important moment of bodily transition: the change from able to disabled body. This semi-autobiographic film follows the story of film director Maud (Breillat’s alter ego), who forms a destructive relationship with a conman, Vilko, after she suffers a disabling stroke. This film shows consistency with Breillat’s previous work in its exploration of the constructed nature of the female body onscreen. In the past the filmmaker has portrayed moments of trauma and transition (such as childbirth, loss of virginity or rape) to subvert processes of objectification. The article argues that Abus de faiblesse challenges and subverts representation of the post-menopausal and disabled body onscreen. The film interrogates binary oppositions such as able/disabled and independence/dependency to challenge representations of the disabled body as ‘other’. With reference to scholarly work on disability and the ageing female body, the article suggests that Maud’s sadomasochistic relationship with Vilko is driven by a quest to retain her subjectivity after her stroke. The article demonstrates that the film dissects the feared and the unknown territory of the ageing female body.